Indian society : institutions and change - Sharma, Rajendra K. (New Delhi : Atlantic, 2004)
"The book highlights the nature and features of Indian Society and the charges that has taken place in various social institutions during different historical phases. This is comprehensive book and covers subjects widely prescribed in the syllabi of various Indian Universities at the Under-graduate and Post-graduate levels in Sociology. The topics covered include Indian Society, Indian Society and Culture, Indian Society and Social Institutions, Social Change in India and Indian Social Institutions, Contemporary Indian Society and Culture. While the subject has been presented in an analytical style with central, side and running headings, integral and holistic view has been adopted, in matters having different opinions. The language is easy and free of technical jargon as far as possible. At the end of each chapter, questions of University examinations have been given to help the students for preparing well for the examination. This ideal textbook will prove most useful to the students, teachers, policymakers and common readers."--
Keywords: Manners and customs; India -- Social conditions